Welfare effects of regional income taxes: Results of an interregional CGE analysis for Germany - Georg Hirte (European Regional Science Association (ERSA), 1998)
This paper deals with the question, whether in a federal state the regions should obtain the right to levy regional income taxes. It is shown that a revenue sharing system influences the optimal income tax rates and causes distortions. In a federal system with other distorting taxes, several states and a revenue sharing system the welfare effects of regional income taxes can be positive or negative due to second best problems. Therefore the welfare effects of regional income taxes are computed by means of an interregional computable general equilibrium analysis (CGE). The results suggest that in the German federal economy the sign of the welfare effects of the introduction of regional income taxes is very sensitive to the particular institutional arrangements.
Keywords: 330